Repositioning of RdRp Inhibitors Against HCV NS5B Polymerase Utilizing Structure-Based Molecular Docking - Tarannum, Heena; Nandi, Sisir (Combinatorial Chemistry & High Throughput Screening, 2022)
Objective: Hepatitis C Virus (HCV) is very dreadful as it can attack an estimated 71 million people around the world. The World Health Organization (WHO) reported that every year about 399000 people die due to HCV caused by chronic cirrhosis and liver cancer globally. There are many drugs available for the treatment of HCV. But drug resistance and toxicity are major issues. The quest for potential drugs utilizing repositioning would be a very useful and economical method to combat HCV. Methods: One of the most common HCV targets is RNA-dependent RNA polymerase (RdRp). The RdRp is common in HCV, Dengue virus (DENV), Zika virus (ZIKV), and Yellow fever virus (YFV) belonging to the same family of Flaviviridae. An attempt has been made in the present study to reposition different DENV, ZIKV, and YFV RdRp inhibitors against HCV NS5B polymerase utilizing structure-based molecular docking which explores the affinity and mode of binding of these RdRp inhibitors. Results: Several 87 compounds having dengue, yellow fever and zika RdRp inhibitory activities have been taken into consideration for the screening of potential RdRp leads utilizing docking simulation, which focuses on the affinity and mode of binding of sofosbuvir diphosphate, a standard HCV, RdRp inhibitor. Conclusion: The compounds 6 (N-sulfonylanthranilic acid derivative), 17 (R1479), 20 (DMB220), 23 (FD-83-KI26), 40 (CCG-7648), 50 (T-1106), 65 (mycophenolic acid), and 69 (DMB213) exhibited docking score within the range of -7.602 to -8.971 Kcal/Mol having almost same mode of interaction as compared to the reference drug molecule. The drugs mentioned above possess satisfactory affinity to bind the hepatitis C viral RdRp and thus may be used to treat the disease. Therefore, these predicted compounds may be potential leads for further testing of anti HCV activity and can be repurposed to combat HCV. The high throughput shotgun of drug repurposing utilizing structure-based docking simulation freeware would be a cost-effective way to screen the potential anti-HCV leads.
Keywords: Hepatitis C Virus (HCV)